Gray Dawn. - Terhune, Albert Payson, 1872-1942. (New York, Grosset & Dunlap, 1961)
Tales of the large, bumptious, silver grey collie whom the Master found either an unbearable nuisance or a grand chum--never knowing which he was due to be next.
Keywords: Collie -- Juvenile fiction; Collie -- Fiction; Dogs -- Fiction